Heinrich Heine en las historias de la literatura alemana en lengua española: 1961-2003 - Borrero, Víctor Manuel (Revista de Filología Alemana, 2007)
The present article’s aim is to deduce the trace of Heinrich Heine in the complete historiography of German Literature conceived for Spanish-speaker readers from 1961 to 2003. The historicalliterary discourse analysis work about the history of literature corpus will allow us not only add data about Heine’s position in this specific canon of 18th and 19th century authors but also realize the canon-making behaviour of German literature as a genre and as a discipline along these years.